Retrotransposons nos genomas de fungos do complexo paracoccidioides: identificação, caracterização, distribuição e expressão - Marco Aurelio Soares (2013)
Evidences from the literature and the previous experience of our research group indicate the occurrence of mobile genetic elements in the genomes of fungi of the Paracoccidioides species complex. Aiming to identify and characterize potentially active retrotransposons in these genomes we employed bioinformatics analysis of the EST deposited in NCBI public databases (www.ncbi.nlm.nih.gov). The 41,558 EST were assembled into a local bank and grouped by sequence alignments, generating 12,922 groups distributed in 8110 singlets and 4812 contigs. These groups were compared with the non-redundant database (NR, NCBI) and databases specialized in transposable elements (TE, RepBase and TEClass), through the BLAST tool. 10,378 groups presented similarity against NR, 142 with retrotransposons characteristic annotator terms as reverse transcriptase (the most common term, with 84 records). In specific banks, 809 groups were found, 342 of which showing regions of similarity to retrotransposons. The remaining 437 were similar to DNA transposons. Only 52 groups were common to both the TE specific and NR banks, and those that showed the highest similarity allowed the identification of five distinct elements in the genomes: - RtPb1, RtPb2, RtPb3, RtPb4 and RtPb5. The elements were characterized and classified in the LTR and LINE orders, superfamilies Copy, Gypsy and I, sustained by phylogenetic analyzes. The coding regions of these elements revealed the presence of characteristic regions corresponding to endonucleases, integrases, proteases, RNases H, reverse transcriptases and a chromo-domain. We identified LTR regions in elements of the Copy and Gypsy superfamilies (RtPb1, RtPb3, RtPb4 and RtPb5) and a poly-A tail LINE-like element (RtPb2). The elements RtPb1 and RtPb2 (Araújo, 2008) had their complete sequences mapped and characterized in silico. The genomic mapping in silico identified 538 copies of all five elements (RtPb1 = 52; RtPb2 = 101; RtPb3 = 18; RtPb4 = 65 and RtPb5 = 302) distributed in the three genomes studied (Pb01= 366; Pb03= 57; Pb18= 115) (www.broadinstitute.org). PCR allowed the amplification of the entire elements by primer walking method. The identity of the elements was confirmed by sequencing and alignment of the reverse transcriptase regions. The sequences were used to verify the presence of each element in the DNA of 31 different fungal isolates. Southern blots analysis of genomic DNA in isolates representative of each of the four known phylogenetic species indicated their presence in multiple copies. The expression of distinct retrotransposons was studied by RT-PCR and by quantitative qRT-PCR. The most expressed element is RtPb1 in isolate Pb01. The analysis showed different expression patterns between distinct fungal isolates. It was observed a peculiar expression of each different retrotransposon in fungal isolates each representative of a known and distinct phylogenetic species.